Pendugaan Biomassa Pohon Berdasarkan Model Fractal Branching pada Hutan Sekunder di Rantau Pandan, Jambi - Prijanto Pamoengkas; Meine van Noordwijk; I Indrawan (Institut Pertanian Bogor (IPB University), 2000)
Fractal branching analysis is a model of indirect estimation on tree biomass that based on the diameter and length of branches. This model put on assumption that the stem diameter before and after branching have the same value which formulated into functional relationship Y = a Db. The research aimed to find out the equation estimation of rubber trees biomass then compared to the equation of corrected biomass after Brown (1997). From this study, it has been found that the equation of above ground biomass for rubber trees is Y = 0.095 D2.62 and non rubber trees Y = 0.091 D2.59 while the equation of aboveground biomass after Brown (1997) is Y = 0.092 D2.60. Based on that grouping in which fractal branching model as a simulation of the Brown model has resulted the same graph. Beside that, the advantage of using this model is that the weight of stem should not be measured because tree biomass can be estimated by measuring the stem diameter